1971
DOI: 10.1590/1809-43921971012007
|View full text |Cite
|
Sign up to set email alerts
|

Notas sôbre os gêneros Polygonanthus e Anisophyllea

Abstract: Instituto Nacional de Pesquisas da Amazônia INTRODUÇÃOCom os comentários apresentados a seguir, temos o propósito de elucidar um problema obscuro que envolve as relações de afinidade de um grupo de plantas constituído por quatro gêneros -Anisophyllea, Polygonanthus, Combretocarpuse Poga -sendo que o primeiro habita tanto o Velho como c Novo Mundo, o segundo é exclusivamente amazônico e os dois últimos são próprios do Velho Mundo. Trata-se de um assunto muito interessante, relacionado com os problemas de evoluç… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
6
0
1

Year Published

1980
1980
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 0 publications
2
6
0
1
Order By: Relevance
“…Croizat (1943) and Hutchinson (1973) treated Polygonanthus as a separate family, Polygonanthaceae, based on a study by Baehni & Dansereau (1939) that stressed the distinctness of this genus and suggested that Polygonanthus was a Saxifragaceae. Despite these, there is little doubt, on the basis of morphological and wood anatomical evidence, that Polygonanthus fits well in Anisophylleaceae, together with the three other genera that have traditionally been placed there (see Kuhlmann 1944, Pires & Rodrigues 1971, Tobe & Raven 1987b.…”
Section: Taxonomic Historymentioning
confidence: 99%
See 1 more Smart Citation
“…Croizat (1943) and Hutchinson (1973) treated Polygonanthus as a separate family, Polygonanthaceae, based on a study by Baehni & Dansereau (1939) that stressed the distinctness of this genus and suggested that Polygonanthus was a Saxifragaceae. Despite these, there is little doubt, on the basis of morphological and wood anatomical evidence, that Polygonanthus fits well in Anisophylleaceae, together with the three other genera that have traditionally been placed there (see Kuhlmann 1944, Pires & Rodrigues 1971, Tobe & Raven 1987b.…”
Section: Taxonomic Historymentioning
confidence: 99%
“…Taxonomic notes:-Anisophyllea manausensis is the second known tropical American species in this genus. It was said to be different from A. guianensis by its sessile leaves and axillary inflorescences (Pires & Rodrigues 1971). However, based on extensive investigations of herbarium specimens, the two species are not so distinctive in these two characters.…”
Section: Anisophyllea Impressinerviamentioning
confidence: 99%
“…P. Chai s.n. in 1981 Kuhlmann, 1944;Pires & Rodrigues, 1971;Van Vliet, 1976). Of the four genera of this family, Anisophyllea is relatively widely distributed in tropical Africa and Asia, also occurring in tropical South America; Combretocarpus is restricted to West Malaysia, Poga to tropical West Africa;…”
mentioning
confidence: 99%
“…A traditional view, and the one most widely accepted, is that Anisophylleaceae have close affinities with Rhizophoraceae, and they often have been considered a tribe or subfamily within a broadly conceived Rhizophoraceae (Bentham & Hooker, 1865;Baillon, 1877;Schimper, 1893;Melchior, 1964;Pires & Rodrigues, 1971;Geh & Keng, 1974;Van Vliet, 1976;Takhtajan, 1980). Even when they have been treated as a distinct family, Anisophylleaceae have generally been considered closely related to Rhizophoraceae (Ridley, 1922;Corner, 1940).…”
mentioning
confidence: 99%
“…Estudos mais recentes sobre os referidos gêneros tentam esclarecer suas relações de afinidades: Pires & Rodrigues (1971) acharam os dois gêneros muito parecidos quanto ao aspecto macroesi_rutural das madeiras e enquadraram o gênero Polygonanthus, possivelmente, também em Gynotrocheae, Grupo II da classificação de Marco (i.e.). Prance et al (1975), na mais recente revisão taxonômica das espécies amazônicas de Rhizophoraceae, trataram os gêneros Anisophyllea e Polygonanthus entre os cinco gêneros da família, que foram estudados, corroborando assim as opiniões de Baillon (1877) e Kuhlmann( 19^*0 quan_ to ã posição dos referidos gêneros na família Rhizophoraceae.…”
unclassified